Outcomes and complications of naftopidil versus tamsulosin for elderly men with lower urinary tract symptoms secondary to benign prostatic hyperplasia: A systematic review and meta‐analysis. (30th June 2021) - Chai, Yumeng; Zhou, Zhongbao; Cui, Yuanshan; Che, Xuanyan; Zhang, Yong
Abstract: We conducted a systematic review and meta‐analysis to assess the outcomes and complications of naftopidil in treating elderly men with lower urinary tract symptoms secondary to benign prostatic hyperplasia and compared them with those administered with tamsulosin. A literature review was performed to identify the available randomised controlled trials concerning the comparison between naftopidil and tamsulosin for men with LUTS/BPH. We searched the following databases: the Cochrane Library Database, PubMed, Embase and Web of Science. Eleven publications involving 1, 114 men (557 in the naf group and 557 in the tam group) were pooled in our analysis. We found no significant differences in the total IPSS, IPSS storage score, IPSS voiding score, quality of life index, peak urinary flow rate, average flow rate and post‐void residual volumes. We assessed cardiovascular and sexual adverse events, acute urinary retention, surgical intervention, withdrawals due to any reason and withdrawals due to adverse events. The incidence of adverse events was similar among patients in naf and tam groups. In conclusion, naftopidil shared comparable efficacy and similar incidence of adverse events with tamsulosin and appears to be a promising agent for and alternative to tam. However, more prospective trials with high quality and long‐term treatment duration are needed to verify this observation.